Deixis Analysis in Disney’s Song - Anggraeni, Layliya; Kareviati, Evie (PROJECT (Professional Journal of English Education), 2025)
The objectives of this study are to find out the use of five types of deixis on Disney’s song. The researcher chooses three songs, there are A Whole New World as a soundtrack of Alladin, Let it Go as a soundtrack of Frozen film and I See the Light as a soundtrack of Tangled. This paper used the qualitative method. The researcher used data collected by listening to the songs and reading the lyrics, then she looked for the script of the lyrics of Disney songs on the internet then analyzed them. After collecting the data, she analyzed the result of this research that not all songs of Disney used five types of deixis. There are personal social, place, time, and discourse deixis. From three songs she just found two songs that used all of the types of deixis. There are in the song A Whole New World and Let it Go. In A Whole New World, there were found 39 words of deixis. In the song Let it Go it is found 42 words of deixis. And in the song, I See The Light there are 55 words of deixis. So, it can be concluded that the most dominant deixis in Disney’s song is in the lyrics of the song I See The Light as a soundtrack of Tangled. The result of this research shows that the most dominant of types deixis in Disney’s song is person deixis.